2010
DOI: 10.1158/1535-7163.mct-09-0495
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inhibition of Histone Deacetylases Sensitizes Malignant Cells to Death Receptor Ligands

Abstract: Evasion of death receptor ligand-induced apoptosis represents an important contributor to cancer development and progression. Therefore, molecules that restore sensitivity to death receptor stimuli would be important tools to better understand this biological pathway and potential leads for therapeutic adjuncts. Previously, the small-molecule 4-(4-chloro-2-methylphenoxy)-N-hydroxybutanamide (that we propose be named droxinostat) was identified as a chemical sensitizer to death receptor stimuli, decreasing the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 44 publications
2
33
0
Order By: Relevance
“…In this study, we provide evidence that HDAC6 is a key deacetylase for Ku70 as, in addition to Vorinostat (inhibitor of HDAC1-3, 6 and 8) 15 and Droxinostat (inhibitor of HDAC3, 6 and 8), 14 the HDAC6-specific inhibitor Tubacin 19 potently increased the acetylation of Ku70. Moreover, both Droxinostat and Tubacin also caused rapid FLIP downregulation.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In this study, we provide evidence that HDAC6 is a key deacetylase for Ku70 as, in addition to Vorinostat (inhibitor of HDAC1-3, 6 and 8) 15 and Droxinostat (inhibitor of HDAC3, 6 and 8), 14 the HDAC6-specific inhibitor Tubacin 19 potently increased the acetylation of Ku70. Moreover, both Droxinostat and Tubacin also caused rapid FLIP downregulation.…”
Section: Discussionmentioning
confidence: 80%
“…To identify the HDACs involved in regulating Ku70 acetylation, we used the HDAC inhibitor Droxinostat, 14 which, although less potent, has a more restricted activity than SAHA: Droxinostat is an inhibitor of HDACs 6 and 8, and (to a lesser extent) HDAC3; 14 SAHA inhibits HDACs 1, 2, 3, 6 and (to a lesser extent) 8.…”
Section: Resultsmentioning
confidence: 99%
“…HDAC8 has been well studied and thus was used as a prototype of HDACs (8,38). The results suggested that CQ was well docked into the active pocket of HDAC8 (Fig.…”
Section: Effects Of Clioquinol On Expression Of Histone Deacetylases-mentioning
confidence: 94%
“…Interference with protein turnover or receptor trafficking, e.g. by application of proteasome inhibitors like bortezomib or protein deacetylase inhibitors, has been shown to increase either death receptor availability or to decrease the availability and function of inhibitory molecules like cellular FLICE-inhibitory protein [118,119,120,121,122]. …”
Section: Novel Compounds Enhancing Cell Death Responsesmentioning
confidence: 99%